Research on Battery Technology of Borohydride New Hydrogen Energy Material. Issue 2 (March 2021) - Fu, Long
Abstract: Vehicle-mounted hydrogen storage is a "bottleneck" link in promoting the large-scale commercial application of hydrogen fuel vehicles. The development of high-performance vehicle-mounted hydrogen storage material technology has become a hot spot in the current energy and materials field. In recent years, with the continuous expansion of the field of hydrogen storage materials, high-storage coordination metal hydrides represented by lithium borohydride ( LiBH 4 ) have gradually become a new research focus of hydrogen storage materials. This article summarizes the latest modification research and application of metal borohydride hydrogen storage materials from the perspectives of substitution, recombination, doping, nanostructure confinement and corresponding reaction mechanism, and puts forward the existing problems and corresponding countermeasures, and points out the future research direction.